Automated screening devices for vision screening in preschool children: A comparison of the PlusoptiX S12C photoscreener and retinomax K+3 autorefractor - Hunter, Stephen C.; Suh, Donny W.; Molina, Iliana; Espinoza, Jennifer (Frontiers in Ophthalmology, 2022)
Automated vision screening devices such as photoscreeners and autorefractors have been used to accurately identify amblyopia, refractive amblyopia risk factors (ARFs), and refractive error in young children; however, there is conflicting data about the effectiveness of different screening devices. We compared the performance of two commercially available screening devices in preschool children. Children aged 3 to 5 years attending 5 preschools in Anaheim Elementary School District were screened with the PlusoptiX S12C photoscreener using ROC 3 referral criteria and Retinomax K+3 autorefractor in March 2022. Screened children were offered free cycloplegic eye examinations performed by optometrists on the UCI EyeMobile for Children mobile clinic. Children were evaluated for the presence of refractive ARFs using 2021 American Association for Pediatric Ophthalmology and Strabismus age-based referral criteria guidelines for instrument-based screening. A total of 158 children were screened and 79 children received cycloplegic examinations. At least one refractive ARF was found in 20% of examined children, corresponding to a sensitivity/specificity/positive predictive value (PPV)/negative predictive value (NPV) of 94%/89%/68%/98% for the PlusoptiX and 100%/65%/42%/100% for the Retinomax. In detecting refractive ARFs, the PlusoptiX was found to have a higher specificity and PPV while the Retinomax had a higher sensitivity and NPV. While both devices demonstrated a high sensitivity and NPV, we found that the PlusoptiX performed better overall as a screening device for our program as the Retinomax referred too many children.